ANALISIS MODEL MATEMATIKA SEIRS TERHADAP KECANDUAN GAME ONLINE SISWA SMPN 3 MANDREHE BARAT - Waruwu, Nove Susanti; Panjaitan, Dedy Juliandri; Firmansyah, Firmansyah (Universitas Methodist Indonesia, 2024)
This research uses documentation and experimental methods. The documentation method is used to create and develop the SEIRS model in cases of online game addiction. Meanwhile, the experimental method is a research method to find answers or solutions to a case or research object. This research was conducted on students in class VIII UPTD SMP Negeri 3 Mandrehe Barat with a total of 26 students within 14 days. In this study, researchers modeled cases of online game addiction into the SEIRS model using the 5th-order Runge-Kutta method so that its effectiveness was obtained based on the data obtained. The results of this study show that the Runge Kutta method is the most effective in the Seirs mathematical model for online game addiction.